Factors influencing maternal nutrition practices in a large scale maternal, newborn and child health program in Bangladesh - Nguyen, Phuong Hong; Sanghvi, Tina; Kim, Sunny S.; Tran, Lan Mai; Afsana, Kaosar; Mahmud, Zeba; Aktar, Bachera; Menon, Purnima (Public Library of Science, 2017)
This paper examines the maternal, household, and health service factors influencing maternal nutrition practices in the context of a large scale maternal, newborn, and child health (MNCH) program in Bangladesh. Data were from a household survey of pregnant (n = 600) and recently delivered women (n = 2,000). Multivariate linear and logistic regression analyses were used to examine the determinants of three outcomes: consumption of iron and folic acid (IFA) tablets, calcium tablets, and diverse diets.